Interação de Macrophomina phaseolina com sementes de feijão-comum - Souza, Nárcya Trindade de (2025)
Common bean (Phaseolus vulgaris L.) production is of great economic and social importance in Brazil, but seed health is a limiting factor for productivity. Among the associated pathogens, Macrophomina phaseolina stands out, the causal agent of charcoal rot, capable of infecting several species. It can be transmitted by seeds or microsclerotia, resistant structures present in the soil and crop residues, which hinder the pathogen's eradication. This study aimed to evaluate the effects of M. phaseolina on bean seeds and determine the rate of transmission of this pathogen from seeds to progeny. For this purpose, seeds of the cultivar TAA-DAMA were inoculated with two isolates of the pathogen, CMLAPS859 and CMLAPS860, for periods of 24, 48, 72 and 96 hours, corresponding to the inoculum levels NI24, NI48, NI72 and NI96. The evaluations were conducted in the laboratory for germination, health, electrical conductivity tests and in plant growth chambers, with controlled temperatures (23°C and 27°C), for the variables: emergence speed index, initial and final stand, seedling height, dry shoot weight, dry root weight, root size, disease index and transmission rate, for 28 days. A direct relationship was observed between increasing inoculum and damage severity. Isolate CMLAPS859 caused greater mortality and reduced plant development, negatively affecting height, shoot dry weight, root size and dry weight, and higher disease rates, with 100% pre-emergence death at the highest inoculum level and transmission exceeding 91.5% in NI24. Isolate CMLAPS860 caused less severe and progressive damage, with 71.3% transmission in NI24, negatively affecting germination rates, ESI, and initial and final stands, but allowing plant establishment, which showed decreased developmental variables. Understanding the dynamics of M. phaseolina transmission via seeds provides support for seed certification and quality control programs in Brazil.